PENINGKATAN KETERAMPILAN MENULIS PUISI DENGAN MENGGUNAKAN KARTUN AKROSTIK PADA SISWA MADARASH IBTIDAIYAH - ST. Aminah Basri; Tasrif Akib; Anzar (LPPM Universitas Muhammadiyah Bulukumba, 2024)
The main problem in this research is how to apply the use of acrostic cartoons to improve fourth grade students' poetry writing skills. This research aims to improve poetry writing skills by using acrostic cards in class IV students of Madrsah Ibtidaiyah (MIN) 1 Jeneponto. This type of research is class action research (Class Action Research) which consists of 2 cycles where each cycle is carried out in 4 meetings. Research procedures include planning, implementing actions, observing and reflecting. The subjects in this research were 15 class IV students of Madrsah Ibtidaiyah (MIN) 1 Jeneponto. The results of the research showed that in cycle I, of the 15 students who completed it individually, only 7 students met the minimum completion criteria of KKM 70 or were in the very low category. Classically it has not been fulfilled because the average score obtained was 46.6%, whereas in cycle II where out of 15 students there were 12 people who had fulfilled the KKM 70 and classically it had been fulfilled, namely the average score obtained was 80% or was in the category tall. Based on the results of the research above, it can be concluded the results of the poetry writing skills of class IV students of Madrsah Ibtidaiyah (MIN) 1 Jeneponto. through the use of acrostic cartoons has increased.